2019
DOI: 10.1007/s10490-019-09654-4
|View full text |Cite
|
Sign up to set email alerts
|

Can institutionalized workplace structures benefit senior women leaders?

Abstract: Drawing on interviews conducted with a sample of 27 senior women leaders from across Australian industries, this study found that legitimate workplace structures disrupt and challenge the subliminal status effects of gender on perceived task or role performance. This related to structures such as increased opportunities for promotion into higher status roles and opportunities to participate in unstructured group-task roles. These findings were in stark contrast to traditional workplace structures where senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…The latter may be an indication that women need more assistance with digital strategies than their male counterparts. Research has also shown that males are more likely to seek 'technical' roles whereas women are less likely to engage in IT skill building which is evident from their tendency to pursue 'softer' technology roles [33,92]. In the context of this study, clearly women recognise the importance of and engaging in social media to build their businesses.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The latter may be an indication that women need more assistance with digital strategies than their male counterparts. Research has also shown that males are more likely to seek 'technical' roles whereas women are less likely to engage in IT skill building which is evident from their tendency to pursue 'softer' technology roles [33,92]. In the context of this study, clearly women recognise the importance of and engaging in social media to build their businesses.…”
Section: Discussionmentioning
confidence: 73%
“…Research indicates that due to the pandemic, gender inequality is more pronounced in terms of digital access, ownership of digital devices, as well as digital fluency [29,30], which has created a perfect storm for women-led SMEs [31,32]. Research also highlights a lack of participation in technical jobs including the need to increase mentoring strategies for women at work [33].…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by other studies, HR practices such as leadership development and mentoring programs and the existence of role models for women within the organization (Fitzsimmons et al, 2014;Murray and Southey, 2020) are highly valued by women respondents. However, these practices appear to be scantily present in the organizations investigated.…”
Section: Discussionmentioning
confidence: 89%
“…Organizations will increase their social legitimacy and chances of survival by conforming to structures and practices accepted in their fields (Suchman, 1995). Institutionally prescribed organizational structures and practices that purport workplace gender equality are expected to disrupt gender bias against women reaching senior positions and should reduce the need for women to gain legitimacy by relying on their personal strengths alone (Lucas, 2003; Murray and Southey, 2020). In the past decade, Japanese businesses have faced significant institutional pressures from the government, investors and foreign institutions, which have indeed led to more women managers being hired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation